MITOS DALAM RITUAL SONGKABALA MASYARAKAT GALESONG KABUPATEN TAKALAR (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
He aim of this research is to describe the myths in the Songkabala ritual of the Galesong people of Takalar Regency. The results of this research show that in the songkabala ritual process of the Galesong community of Takalar Regency, it has (1) denotation meaning, namely Unti teknek/sweet banana, jepek/porridge, bente, dupa, tai bani/liling, songkolok, bayao/egg, tumpi-tumpi, jeknek Kaluku / Coconut water, Doek / Money. Meaning (2) connotation, namely Unti teknek/sweet banana means the path of life will be sweet, Jepek/porridge means life will be happy, Bente means having abundant fortune, Dupa, Tai bani/ Liling to illuminate people's lives, Songkolok, Bayao/ Eggs , Tumpi-tumpi, Jeknek kaluku / Coconut water, Doek / Money. The meaning of (3) myths is that Unti teknek/Sweet banana means that there will be a series of disasters, Jepek/Push means life will not be happy, Bente means not having sustenance, Dupa means all bad things will go away, Tai bani/Liling has no brightness in life, Songkolok means that the family will fall apart and not find a soul mate, Bayao/Egg if the egg is cracked, it is a sign that someone wants to do evil, Tumpi-tumpi means avoiding disaster in any way, Jeknek Kaluku/Coconut water has a heart that is not dirty, Doek/Money, It was interpreted by the community as not feeling good towards Panrita